Ultraflexible organic light-emitting diodes for optogenetic nerve stimulation - Kim, Dongmin (Proc Natl Acad Sci U S A, 2020)
Organic electronic devices implemented on flexible thin films are attracting increased attention for biomedical applications because they possess extraordinary conformity to curved surfaces. A neuronal device equipped with an organic light-emitting diode (OLED), used in combination with animals that are genetically engineered to include a light-gated ion channel, would enable cell type-specific stimulation to neurons as well as conformal contact to brain tissue and peripheral soft tissue. This potential application of the OLEDs requires strong luminescence, well over the neuronal excitation threshold in addition to flexibility. Compatibility with neuroimaging techniques such as MRI provides a method to investigate the evoked activities in the whole brain. Here, we developed an ultrathin, flexible, MRI-compatible OLED device and demonstrated the activation of channelrhodopsin-2–expressing neurons in animals. Optical stimulation from the OLED attached to nerve fibers induced contractions in the innervated muscles. Mechanical damage to the tissues was significantly reduced because of the flexibility. Owing to the MRI compatibility, neuronal activities induced by direct optical stimulation of the brain were visualized using MRI. The OLED provides an optical interface for modulating the activity of soft neuronal tissues.